“I Wish You Had Died on Utøya”: Terrorist Attack Survivors’ Personal Experiences with Hate Speech and Threats - Glad, Kristin Alve (Terrorism and political violence, 2024)
We aimed to explore how many of the politically active, highly media-exposed, young survivors of the terrorist attack on Utøya island, Norway, have had personal experiences with hate speech and threats post-terror. Further, we aimed to examine the nature of these experiences, and the impact and consequences they have had for the directly affected. Approximately 8.5 years after the politically motivated terrorist attack on Utøya island in 2011, 289 survivors (51.2 percent females, M age = 27.7, SD = 4.6) were interviewed about their personal experiences with hate speech and threats. Responses were systematically analyzed using thematic analysis. In total, ninety-nine participants (34 percent) had experienced hate speech and/or threats post-terror, of whom a majority believed that this was related to their status as a survivor of the attack. Thematically, the hate/threats mainly revolved around wishes that the survivors had died in the attack, death threats, support for the terrorist, severe accusations related to the attack, and conspiracy theories. This had affected the survivors both emotionally (e.g., inducing fear and anger, but also robustness) and behaviorally (e.g., social and political withdrawal). Immediate measures and long-term strategies need to be developed to mitigate the personal harm and threat to democracy that experiences with hate speech/threats may cause.